A study of unusually heavy to very heavy rainfall over Kerala in October 1999 - LAKSHMINARAYANAN, R.; RAJAMOHAN, R. (MAUSAM, 2003)
Kerala received heavy to very rainfall in October 1999 being a record rainfall of 54.6 cm of the twentieth century for the month of October. A few stations in central Kerala like Punalur, Alappuzha, Kottayam, Konni, Aryankavu, Chertala, Thodupuzha and Mannarghat reported record October month rainfall of the twentieth century. Synoptic features responsible for these heavy rains have been examined. It was found that favourable position of the east-west trough/shear line running across latitude 10° North in the lower and middle troposphere and the strengthening of westerly winds over Lakshadweep and south Kerala in association with systems moving across north Andaman Sea and east central Bay are the prime causes leading to heavy to very heavy rainfall in October 1999 over Kerala for about 20 days in October.